Adaptive pathway of summer maize under drought stress: Transformation of root morphology and water absorption law - Yan, Siying; Weng, Baisha; Jing, Lanshu; Bi, Wuxia; Yan, Denghua (Frontiers in Earth Science, 2022)
The adaptability of crops reflects the ability to continue to grow in the changing environment. Its adaptability in adversity plays an important role in its own growth and development. The root system is the main organ for crops to absorb water and nutrients, it can adjust its own morphology, physiological, biochemical to improve its water absorption and thus adapt to drought stress. Previous studies mostly focused on the above ground part of crops, but less on the underground part of crops due to the complexity of root observation. In order to study the adaptability of summer maize under different drought conditions, taking 'Denghai 618' as the experimental material, with prototype observation and micro root window as technical support, under the ventilation shed, two treatment groups of light drought (LD) and moderate drought (MD) and the same rehydration after drought are set, as well as the normal water supply for control inside the shed (CS) and Control outside the shed (COS). The changes of root morphology and the law of root water absorption under drought and Rehydration after different drought were analyzed. The results showed that: (1) Under drought stress, the root system of maize adapts to drought by thinning and increasing fine roots to improve root water absorption. Under the MD, the root adaptation to drought is more obvious: promoting root growth. Root biomass was no significant difference between the drought treatment group and the CS. The root biomass of the drought treatment group was significantly lower than that of the COS due to the thinner root system. (2) The total amount of root water absorption in the CS and COS increased steadily with the increase of days. In the drought treatment group, the root water absorption decreased with the increase of drought degree, that is, COS > CS > LD > MD. This study provides a reference for revealing the self-adaptive regulation mechanism of summer maize roots under drought conditions.